Transfer of Undertaking Protection of Employment: Ideas and Praxis - Syahwal, Syahwal; Rofi Wahanisa; Septhian Eka Adiyatma; Alleandria La Graha (Universitas Negeri Semarang, 2024)
The discussion in this article departs from the issues about the continuity of work of outsourced workers who are trying to be protected by the principle of Transfer of Undertaking Protection of Employment. The articles were prepared non-doctrinally in order to address the issue by incorporating outsourced workers by using the interview method and the statute approach. As a result, the TUPE principle failed to provide protection to outsourced workers. Which failure results from the practice of terminating the work agreement when the contract of business cooperation ends. Furthermore, the protection of the continuity of work for outsourced workers is based only on the moral obligations of the new outsourcing company. Based on the causes of this failure, the development of labour law must impose legal obligations on new outsourcing companies by incorporating the TUPE clause into the contract of business cooperation between the outsourcing company and the user company.